Challenges and development of contemporary islamic da'wah in Japan, South Korea, and Taiwan - Yuwono, Ardi Tri; Sebastian, Andi; Rahman, Haru; Chung-Hee, Amir; Chen, Abdullah (Jurnal Ilmu Dakwah, 2025)
Purpose – This study aims to identify various challenges and developments of contemporary Islamic da'wah in Japan, South Korea, and Taiwan. Method – This research relies on a qualitative approach with a literature study method, where data is collected through searching written sources such as books, academic journals, news articles, historical documents, and online publications related to the development of Islamic da'wah in Japan, South Korea, and Taiwan. Result – Da'is (Islamic preacher) in Japan, South Korea, and Taiwan face several challenges in spreading Islam, such as: (1) The World Trade Center incident in the United States on September 11, 2001 which negatively impacted the image of Islam among East Asia society; (2) Problems related to funerals; (3) Difficulty in finding a place to perform ablution; (4) Difficulties in integrating Islamic values into East Asia traditions, and; (5) The difficulty of the older generation in passing on Islamic knowledge to the younger generation. Implication – This research could encourage: (1) Train and empower Muslim youth in the region so that they can develop a da'wah approach that integrates Islamic teachings with culture and technology, as well as have broad insights and always follow the latest developments; (2) Understand the characteristics, interests, and needs of the local community; (3) Linking Islamic teachings to relevant social issues and offering inspiring solutions, and; (4) Muslims in the region are expected to demonstrate good behaviour and be consistent with the Islamic teachings they preach. Originality/Value – The novelty of this study lies in the more comprehensive and up-to-date presentation of the dynamics of Islam in East Asia, especially related to da'wah challenges and strategies in Japan, South Korea, and Taiwan. With a focus on a wide period, from 1950 to 2025, this study not only provides insight into the changing attitudes and acceptance of Islam by society but also presents recommendations for developing more effective da'wah strategies in the future. *** Tujuan – Penelitian ini bertujuan untuk mengidentifikasi berbagai tantangan dan perkembangan da'wah Islam kontemporer di Jepang, Korea Selatan, dan Taiwan. Metode – Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur, di mana data dikumpulkan melalui pencarian sumber tertulis seperti buku, jurnal akademik, artikel berita, dokumen historis, dan publikasi online yang berkaitan dengan perkembangan da'wah Islam di Jepang, Korea Selatan, dan Taiwan. Hasil – Da'is (penyebar ajaran Islam) di Jepang, Korea Selatan, dan Taiwan menghadapi beberapa tantangan dalam menyebarkan Islam, antara lain: (1) Insiden World Trade Center di Amerika Serikat pada 11 September 2001 yang berdampak negatif terhadap citra Islam di masyarakat Asia Timur; (2) Masalah terkait upacara pemakaman; (3) Kesulitan menemukan tempat untuk berwudhu; (4) Kesulitan mengintegrasikan nilai-nilai Islam ke dalam tradisi Asia Timur, dan; (5) Kesulitan generasi tua dalam meneruskan pengetahuan Islam kepada generasi muda. Implikasi – Penelitian ini dapat mendorong: (1) Melatih dan memberdayakan pemuda Muslim di wilayah tersebut agar dapat mengembangkan pendekatan da'wah yang mengintegrasikan ajaran Islam dengan budaya dan teknologi, serta memiliki wawasan yang luas dan selalu mengikuti perkembangan terbaru; (2) Memahami karakteristik, minat, dan kebutuhan masyarakat lokal; (3) Menghubungkan ajaran Islam dengan isu-isu sosial yang relevan dan menawarkan solusi yang inspiratif, dan; (4) Muslim di wilayah tersebut diharapkan menunjukkan perilaku yang baik dan konsisten dengan ajaran Islam yang mereka ajarkan. Orisinalitas/Nilai – Keunikan studi ini terletak pada penyajian yang lebih komprehensif dan terkini mengenai dinamika Islam di Asia Timur, terutama terkait tantangan dan strategi dakwah di Jepang, Korea Selatan, dan Taiwan. Dengan fokus pada periode yang luas, dari 1950 hingga 2025, penelitian ini tidak hanya memberikan wawasan tentang perubahan sikap dan penerimaan Islam oleh masyarakat tetapi juga menyajikan rekomendasi untuk mengembangkan strategi dakwah yang lebih efektif di masa depan.